Application of Vermicompost and Microbial Solution: Efforts to Increase Growth and Yield of Pagoda Mustard Greens (Brassica narinosa) - Mohammad Sholeh; Istirochah Pujiwati; Sugiarto Sugiarto; Nurhidayati Nurhidayati (AGRONISMA, 2022)
The production of green mustard in Indonesia always increase totally year to year, along with the enhancing consumption of vegetables in the community. Therefore, the alternative hydrogenic cultivation efforts are needed. This study aims to determine the interaction between the dose of vermicompost and the concentration of microbes on the growth and yield of Pagoda mustard (Brassica narinosa). In addition, this study was a pot experiment using a factorial randomized block design (RAK) whereas factor I: vermicompost dose (0, 100, 200, 300 g/pot) and factor II microbial concentration (0. 25, 50 ml/liter). The results of this study showed that no significant interaction between the two factors on plant growth and yield. Other than that, Vermicompost application of 200 g/pot gave the best number of leaves and leaf area of 27.17 pieces and 273.75 cm2, respectively. The harvest consumed is 45.85 g/plant or 0.67 t/ha. Microbial concentration of 50 m/liter gave high yields but was not significantly different from that without microbial application.